VD_FINDINFO Jug / 2013 / 12 vom 28. März 2012 - VD Tribunal cantonal (2012)
TORT MORAL, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE, FIXATION DE LA PEINE, DÉPENS | 49 CO, 43 CP, 47 CP, 429 CPP (CH), 430 CPP (CH), 433 al. 1 CPP(CH)